Pengaruh Green Marketing Dan Consumer Awareness Terhadap Purchase Decision Pada Industri Fast Moving Consumer Goods - Tjan, Selly Beauty Wahayu; Rudy P. Tobing (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
Comfort, practicality and efficiency are important things in the human process of meeting daily needs. One of the impacts of meeting these needs is that single-use plastic is temporary and difficult to decompose, thereby worsening environmental problems. Various concerns raise awareness and bring innovation to save the environment. Siklus Refill is one of the innovators of household product refill services. However, the number of Siklus Refill consumers is still not optimal compared to the number of followers on social media. This research aims to determine the influence of green marketing and consumer awareness on purchase decisions in the Fast Moving Consumer Goods Industry which is studied from the perspective of Siklus Refill consumers in South Jakarta. This research was conducted using a quantitative approach with a sample size of 62 respondents. The instrument used in this research was a questionnaire. Instrument testing includes validity tests and reliability tests. Data analysis uses descriptive analysis, while hypothesis testing uses multiple linear regression analysis along with the T test, F test and R2 test. The research results show that (1) green marketing has an effect on purchase decisions, (2) consumer awareness has no effect on purchase decisions, (3) green marketing and consumer awareness simultaneously have an effect on purchase decisions.